Industrial crisis, X and Y factors, organizations - Duchoň, Bedřich (Univerzita Pardubice, 2010)
The financial crisis has created an industrial crisis. The typical example of this fact is the almost zero cost of fuel and handling in the shipping containers and freights. Half-empty freighters bring the signal of a worldwide collapse of manufacturing. Industrial production fell in USA, Great Britain and Europe, in Brazil, China. The manufacturing is still seen and understood as a nationalistic problem, in fact has also the global character. In spite of financial and economic crisis, the society depends on technological development, especially on new innovations. To provide the technical innovations means to have organizations, social-economic systems that are able to create new management approaches. The proposal will be dedicated and aimed at new approaches of factors X and Y as well as to managerial strategy.
Keywords: crisis; finance; industry; transport; manufacturing; innovation; theory X, Y; organization